Alih Bahasa Dan Reliabilitas Paediatric Sleep Questionnaire Terhadap Anak Usia 6-18 Tahun (Laporan Penelitian) - Siti Chandra Dwidjayanti; Mufidah Nurul Hayati; Carolina Damayanti Marpaung (Fakultas Kedokteran Gigi Universitas Trisakti, 2021)
Background: Obstructive Sleep Apnea (OSA) is a common type of Sleep-Related Breathing Disorder (SRBD) defined as a cessation of airflow at the nose and mouth enduring for a minimum of ten seconds. The awareness absences of this condition particularly in children will contribute to the growth and development abnormality which effected their adulthood. The difficulty in diagnosing SRBD/OSA’s children with Polysomnography (PSG) as a Gold Standard is another challenging issue due to the inconvenience and the high cost. Recent studies have reported the possibility of screening this condition with Questionnaires contains items of SRBD signs. Pediatric Sleep Questionnaire (PSQ) was one of the most frequently used questionnaire in this screening processed. Purpose: The study aims were to translate PSQ into the Indonesian language and measuring the reliability of the questionnaire. Methods: PSQ translated with a forward-backward translation technique and analytic observational with the cross-sectional design was conducted at school placed in Tangerang City with 154 respondents age 6-18 years old who fulfilled inclusion and exclusion criteria. Cronbach’s alpha was used to measure the reliability of each item question. Results: The Cronbach’s alpha for this study was 0,714 which was reliable for this questionnaire to be used for screening patients with SRBD. Conclusion: This study showed that the PSQ has good reliability which can be more optimized to diagnosed SRBD in children together with PSG.